Intervención temprana en niños con deficiencia visual de 3 a 5 años que asisten al instituto especial fiscal para ciegos Byron Eguiguren - Correa Cueva, Carla Jaqueline (2018)
The present thesis work, entitled EARLY INTERVENTION IN CHILDREN WITH VISUAL DEFICIENCY FROM 3 TO 5 YEARS OLD THAT ATTEND TO THE SPECIAL FISCAL INSTITUTE FOR THE BLIND '' BYRON EGUIGUREN ''. The present research work was applied in response to the reality that children with visual disability live, since that disability is a sensory limitation or the complete absence of the ability to see, which causes important difficulties to visually identify both people and objects and also to locate and orient themselves in the environment and their characteristics. Within the types of disability there are: deep, that represents disability to perform gross visual tasks or impossibility to perform detailed vision tasks; severe, performs visual tasks with inaccuracy and requires time to execute a task; Moderate, performs tasks with the support of lenses and lighting. In this context, the following general objective was proposed: to contribute with the application of an early intervention project to visual impaired children from 3 to 5 years old who attend to the Special Fiscal Institute for the Blind "Byron Eguiguren". The research work was oriented in the action-research, through the intervention, of descriptive character, of explanatory type, of quantitative - qualitative approach. We used methods such as scientific, analytical, inductive and descriptive. We applied the instrument called the Portage Guide of SM Bluma, MS Shearer, AH Frohman and JM Hilliard that allowed us to evaluate the different areas of child development, the population used for the present research was with a case study of 6 children of the special fiscal institute Byron Eguiguren. The activities were applied in an adequate and systematic way, which contributed to improve children’s lifestyle. After the application of the Partague Guide, it was demonstrated that there was an improvement in the different areas such as cognitive, motor, socio-affective and language aspect of the children. Therefore, we recommend the center to continue applying these activities to enhance their learning.